Investment property accounting standard: The other breakthrough a case study of final semester accounting students / Noor Saatila Mohd Isa and Norliana Omar - Mohd Isa, Noor Saatila; Omar, Norliana (Universiti Teknologi MARA, Sabah, 2020)
In this era of technological advancement, there is a tremendous growth in the usage of mobile applications, mainly among accounting students in higher institutions as a medium for learning tools in education. Accounting students at tertiary level basically are subjected to learn different types of accounting standards. Accounting standards have continued to evolve to strike the balance between providing meaningful information to the users and balancing up cost of preparing such information. However, there is a growing concern that financial reporting has become overly complex. The complexity caused by financial reporting standards may derive from many factors, such as their length, the difficulty in understanding them, and the cost of applying their requirements. In the educational stream, students find that it is hard to understand lengthy wordings in the standards. Therefore, this interactive application is designed to help users especially students on classification issues under MFRS140 Investment Property. Hence, the purpose of the study is to prove the practicality and usefulness of mobile apps to understand accounting standards which is known as MFRS140: Quick Chart Mobile App particularly among final semester accounting students. In this study, the results revealed that this application provides useful and precise guidelines for students as to avoid lengthy wordings to increase the level of their understanding. By using the application, users will have a better knowledge in identifying whether the land and buildings fall under MFRS140 or other MFRSs. Furthermore, the application contributes to the effort of making users learn standards of accounting in a different perspective rather than a classroom-oriented perspective.